Induction of oestrus and ovulation in buffalo (bubalus bubalis) using cloprostenol, a synthetic analogue of prostaglandin f₂ᵪ* - Jainudeen, Mohamed Razeen (Persatuan Doktor Veterinar Malaysia, 1976)

(untitled)
The use of cloprostenol ("Fstrumate", I.C.I), a synthetic analogue of prostaglandin F ₂ᵪ for the induction of oestrus and ovulation was studied in 23 lactating swamp buffaloes (Bubalus bubalis). A dose of 250 or 500μg cloprostenol was administered as a single intramuscular injection between day 5 and 14 of the oestrous cycle. Oestrus occurred 82±8.2 hr. (25Oμg) or 81±10.7 hr (500μg)after cloprostenol treatment in 21 of 23 cows treated. The induced oestrus was followed by ovulation and corpus luteum development in every animal. The pregnancy rate was 48 per cent for the service at the induced oestrus. However, in the absence of control data no conclusions can be drawn on the effects of cloprostenol on fertility.